التباين المكاني لمشاريع البزل في محافظة واسط - ali, nnour (Journal of College of Education, 2022)
AbstractThe irrigation process in the province is a very complex process due to its reliance on pump irrigation And a system of codified streams represented by the streams built on the Tigris River within the boundaries of the governorate The two banks of the right and left river are accompanied in this extension by the drainage projects represented by the excavation projects, Al-Shehimiyyah, Dujaila, the irrigation projects of Al-Dabouni, Badra and Jassan, and the irrigation project of Al-Dalmaj, as well as the presence of tables in the main city of Al Kut represented by the Al Gharraf and Dujaila tables, which are located in front of the Kut dam, so that each of these projects has A special drainage rate, and it works in a dual way represented by ridding the land of the water that is in excess of the plant’s need and then using it again to irrigate the crops. Thus, the irrigation complexity of the governorate and the nature of the efforts required to control water distributions to thousands of participants and the operation of giant pumping crews (for irrigation and drainage) and the periodic maintenance of these systems And establishments that sometimes reach more than two hundred work that need an exceptional effort to achieve them, and accordingly, our study includes four axes, where we dealt in the first axis a history of trocars, the second axis the importance and benefits of puncture, and the third axis the patterns and types of trocars in Wasit governorate and the fourth axis: spatial variation of drainage projects In Wasit Governorate .